Metaverse consulting : future trend or a hype cycle? - Reuss, Henriette (2024)
The Metaverse is experiencing tremendous growth. Companies such as the Big Four and many boutique consultancies are developing use cases, taking on the role of innovators in the market. The thesis aims to analyze the acceptance and application of the Metaverse in the consulting industry. Secondary data was collected through a literature review. The literature depicted the general definition and development of the Metaverse and the implementation of successful use cases conducted by consultancies. As for primary data, qualitative and quantitative research methodologies were combined. The literature review, expert interviews, and survey were triangulated. Analyzed were management models about the technology acceptance, dynamic capabilities, diffusion of innovation, and first mover advantage. The results suggest that despite skepticism around the hype of the Metaverse, long-term interest and potential are observable, especially for the educational sector, heavy industries, and virtual work scenarios. The study highlights that education and the development of praxis-relevant applications are important elements for the successful implementation of the Metaverse in consultancies. Broad acceptance is still pending but increasing within companies, and consultancies are adapting their dynamic capabilities accordingly.